Fracture properties of porous yttria-stabilized zirconia under micro-compression testing. Issue 4 (April 2022) - Abaza, A.; Laurencin, J.; Nakajo, A.; Hubert, M.; David, T.; Monaco, F.; Lenser, C.; Meille, S.
Highlights: Porous ceramic micro-compression samples have been fabricated, tested and characterized. The Young's modulus has been estimated as a function of the porosity. The compressive fracture strength has been measured as a function of the porosity. The transition from a brittle behavior to a diffuse damage has been detected when increasing the porosity. Abstract: Micro-compression tests were carried out on pillars of 60 μm in diameter, milled by plasma focused ion beam in porous Yttria-Stabilized Zirconia (YSZ) pellets. The fracture properties were determined over a wide range of porosities (33 %–63 %) for 8YSZ and at a given pore volume fraction of 63 % for 3YSZ. The mechanical properties determined from testing were reproducible thanks to the homogeneity of the microstructures. The Young's modulus was estimated as a function of the porosity from the unloading curve of tests stopped before fracture. The experiments conducted until the total rupture allowed measuring the compressive fracture strength, which was found to decrease when increasing the porosity. Specimen tested and unloaded just before the total fracture were cross-sectioned by focused ion beam - scanning electron microscope. A transition was detected from a brittle behavior, with macro-cracks parallel to the direction of solicitation, to a diffuse damage with micro-cracks, when increasing the porosity.